Barriers to renewable/sustainable energy technologies adoption: Indian perspective - Luthra, Sunil; Kumar, Sanjay; Garg, Dixit; Haleem, Abid (Renewable & sustainable energy reviews, 2015)
Rapidly increasing energy demand and growing concern about economic and environmental consequences call for renewable/sustainable energy technologies׳ adoption in India. Renewable/sustainable energy technologies have faced a number of constraints that have affected their rate of adoption. In this paper an attempt has been made to identify and rank the major barriers in the adoption of ‘renewable and green’ energy technologies in the Indian context. Twenty-eight barriers have been identified from an extensive literature review. These identified barriers have been categorized into seven dimensions of barriers, i.e. Economical & Financial; Market; Awareness & Information; Technical; Ecological and Geographical; Cultural & Behavioral; and Political & Government Issues. Analytical Hierarchy Process (AHP) technique has been utilized for ranking of barriers to adopt renewable/sustainable technologies in the Indian context. All pair comparisons in AHP have been made based on experts’ opinions (selected from academia and industry). Sensitivity analysis has also been made to investigate the priority ranking stability of barriers to adopt renewable/sustainable technologies in the Indian context. This paper may help practitioners, regulators and academician focus their future efforts in adoption of ‘renewable/sustainable energy technologies’ in India. Further, this understanding may be helpful in framing the policies and strategies towards adoption of renewable/sustainable energy technologies.